Obesity: a global health problem - Jha, Anshu Kumar; Das, Anup Kumar (International Journal Of Community Medicine And Public Health, 2019)
Since time immemorial, obesity has engulfed the mankind. It’s a pandemic. The prevalence is increasing by leaps and bound. Evidences date back to 30,000 BC. Earlier it was linked to wealth and status and it took a long time for it to be considered as a disease. This change in mind-set of the people occurred in mid-19th century. Different formulas for calculating the BMI (Body Mass Index) were invented which was different for the world and the South-East Asians. Slowly it became a topic for research among the scientific society and first priority was given to finding out the cause of obesity. It could not be pointed down to one as many factors were found to contribute to the menace of obesity. Age, gender, genetics, environment, food habits, various co-morbid conditions and the list of contributing factors is endless. Studies done at the molecular level have shown that various cytokines like TNF, Interleukins, Monocyte Chemoattractant Protein, adipokines, etc., have been implicated in the pathogenesis of obesity. The first line in the management of obesity is to take preventive measure. Those who have started to develop the disease should undergo a few non-pharmacological treatment options like lifestyle modification, change in food habits and behavioural therapy. Initially drugs like fenfluramine and sibrutramine were developed. With newer researches coming up more safer and consistent molecules like Tesofensin have been found and undergoing trial. If not benefited by medical treatment the last option what remains for the patient is bariatric surgery but they are too costly for general population to afford. Finally, it is best seen that it is wise enough to follow the saying “Prevention is better than cure” for a disease with such a vast etiology.